2022
DOI: 10.5937/inovacije2203091v
|View full text |Cite
|
Sign up to set email alerts
|

The potential of online platforms compared to in-person teaching: Different experiences of teachers

Abstract: The first part of this paper offers a theoretical interpretation of the previous research of the methodological potential and efficiency of online teaching (especially during the Covid regime), whereas the second part is methodologically oriented towards the examination of the attitudes of teachers on the potential of the implemented distance learning platforms vs. in-person teaching. The sample is represented by 604 teachers of elementary and secondary schools from all administrative regions in the Republic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The research conducted by the end of 2021 points to considerable differences in using tools and platforms when conducting and organising online lessons, reporting the findings that the commonest platforms used for synchronous online teaching were Zoom, Google Meet, and Microsoft Teams, while Google Classroom and Moodle were mainly used as LMS platforms [8]. As regards teachers' perception of the benefits of using digital technologies, opposing results can be found in research -some show that teachers do not express dominantly positive attitudes, prioritising traditional and face-to-face interaction [9], while others identified that the use of technology can facilitate lesson preparation, enhance students' motivation, and make teaching and learning material more accessible to everybody [10]. In research conducted with the aim of examining students' opinions on the possibilities online learning can offer, the results show that secondary students to a high extent recognise the advantages and possibilities of digital tools and platforms [11].…”
Section: Technology-supported Teachingmentioning
confidence: 99%
“…The research conducted by the end of 2021 points to considerable differences in using tools and platforms when conducting and organising online lessons, reporting the findings that the commonest platforms used for synchronous online teaching were Zoom, Google Meet, and Microsoft Teams, while Google Classroom and Moodle were mainly used as LMS platforms [8]. As regards teachers' perception of the benefits of using digital technologies, opposing results can be found in research -some show that teachers do not express dominantly positive attitudes, prioritising traditional and face-to-face interaction [9], while others identified that the use of technology can facilitate lesson preparation, enhance students' motivation, and make teaching and learning material more accessible to everybody [10]. In research conducted with the aim of examining students' opinions on the possibilities online learning can offer, the results show that secondary students to a high extent recognise the advantages and possibilities of digital tools and platforms [11].…”
Section: Technology-supported Teachingmentioning
confidence: 99%